Knowledge and lifestyle practices of hypertensive patients utilizing public and private health sectors in Umlazi Township of KwaZulu-Natal - Simamane, Mandis Jewel (My University, 2018)
Background:The South African government has taken several measures to address the evolving epidemic of non-communicable diseases (NCDs), but so far these efforts have not been effective in preventing the rising burden from these diseases. Hypertension is the most prevalent NCDs in society but unfortunately the control of this disease is suboptimal, and it is a growing health concern in all regions of the world, regardless of income. There is a substantial difference in resource availability between public and private health care sector (HCS) facilities and this result in disturbing impact on the population’s health, resulting in unnecessary morbidity and mortality. Understanding the patient’s knowledge, management of hypertension and its risk factors will help to identify the differences between the patients utilizing public and private health care (HC) providers in managing hypertension. Aims: To determine patient’s knowledge, management of hypertension and its risk factors between the patients utilizing public and private HC providers in managing hypertension. Methods: A cross-sectional study design was conducted in Umlazi Townships in KwaZulu-Natal (KZN); patient’s utilizing strictly public health sectors were compared to those strictly using the private health sectors. Measurements of blood pressure (BP), body mass index, waist-to-hip ratio, as well as hypertensive patients questionnaire, global physical activity question, diet and smoking questionnaire were used as measuring tools and instruments. For normally, distributed continuous data an independent two-tailed t test was used to determine any significant differences (p=≤0.05) and for non-normally distributed or categorical data a chi-square test was used. Results: A total of 137 people consented to participate in this study, comparison of the demographic characteristics was made between participants’ utilizing the public HCS (n=77) and private HCS (n=60). The participants average age was 65 years (±10.83) and 60 years (±9.15), for the public HCS and private HCS, respectively, the public HCS participants were significantly older than those attending private HCS (t=2.41) (p=0.02). The average BMI for the study sample (N=137) was 30.45kg·m2 on both the groups, classified as Obese I. No significance relationship (X2=0.03, p=0.85) was found between the type of HC provider and having been admitted to hospital over the last year, 58.44% and 58.33% participants felt their BP was better compared to 12 months ago, in the public and private HCS, respectively. A significance relationship (X2=3.96, p=0.05) was found between the type of HC provider the participants consulted for their hypertension and taking all prescribed medication, with public HCS (100%) participants being more likely to take their medication compared to the private HCS (95%). On average the participants global physical activity questionnaire total metabolic equivalents per week (t=0.63) (p=0.53) between the public and private HCS was 1803.12 (±4755.96) and 1385.33 (±2295.32), respectively. The public HCS (61.04% and 64.94%) had more participants that smoked regularly for ≥5 years (X2=5.98, p=0.02) and those that drank alcohol as compared to the private HCS (38.33% and 48.33%) (X2=3.81, p=0.05). Conclusion: The participants of the private HCS did not tend to have better knowledge and management of hypertension and its risk factors as compared to that of the public HCS, although there were few differences between the two groups. This suggests that an intervention programme, which invests in area based specific strategies, is recommended, including healthy lifestyle and physical activity, needs to be implemented in the community of Umlazi Township in managing hypertension.
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements of the degree of Master of Science in Medicine (Sport and Exercise Science), Johannesburg 2018
Keywords: Hypertension